Magnesium sulfate prevents the development of forced swim induced hyperalgesia in rats - Rada, Mariana; Cárdenas-Fernández, Ricardo; Guevara, Coram; Cristina Fernández, Ana; Suárez-Roca, Heberto (Investigación Clínica, 2018)
The present study evaluated the effect of magnesium sulfate (MgSO 4) on forced swim-induced thermal hyperalgesia in male Sprague-Dawley rats. Two schemes of MgSO 4 administration were used: a preemptive scheme (100 mg/kg i.p. before each forced swim) and a therapeutic scheme (a single dose of 100 mg/kg, 24 hours after the final forced swim); pharmacological controls received normal saline. Thermal nociception was determined using the hot plate test, and lumbar spinal levels of nitric oxide (NO) metabolites were measured. Thermal hyperalgesia was present in forced swim animals treated with saline before each forced swim, but absent in forced swim animals preemptively treated with MgSO 4. We could not determine an anti-hyperalgesic effect of the therapeutic scheme since MgSO 4 tended to produce analgesia when administered one hour before the hot plate test, probably due to an acute stress response caused by the injection. On the other hand, non-stressed animals preemptively treated with MgSO 4 displayed significantly higher levels of NO metabolites than forced swim animals preemptively treated with MgSO 4 or saline and non-stressed animals preemptively treated with saline. The results suggest that MgSO 4 can prevent the development of persistent pain states, but is unable to revert already established ones, a potential feature in patients suffering from anxiety, depression and chronic stress exposure; likewise, they indicate that the effect of MgSO 4 on nociception is independent of an induction of NO synthesis. Corresponding author: Ricardo Cárdenas-Fernández. Sección de Neurofarmacología y Neurociencias, Instituto